Pengaruh Praktik Kerja Lapangan (Magang) Dan Efikasi Diri Terhadap Kesiapan Kerja Dengan Motivasi Sebagai Intervening Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Tanjungpura - Ricardo, Soni B1021161031 (Jurnal Manajemen Update, 2020)
ABSTRACTThe Subject of this study was to examine the effect of field work practices (internship) and self efication towards work readiness with motivation as intervening on students of Economics and Business Faculty of University of Tanjungpura. The data analysis technique was conducted using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) approach using WarpPLS 6.0 software. The result in this study indicate that (1) field work practices (internships) could not have a significant effect on the work readiness of FEB students of University of Tanjungpura,  (2) self-efficacy and Motivation had a significant effect on work readiness of FEB students of University of Tanjungpura,  (3) field work  practices (internships) and self- efficacy have a significant effecttowards motivation of FEB students of University of Tanjungpura. Keywords: Field Work Practice (Internship), Self-Efficacy, Motivation, and Work ReadinessDAFTAR PUSTAKA Abdillah, W., & Hartono. (2014). Partial Least Square (PLS). Yogyakarta: ANDI Publisher. Adityagana, D. A., Insrawati, C. S., & Rahmanto, A. N. (2018). Pengaruh Praktik Kerja Lapangan dan Efikasi Diri terhadap Kesiapan kerja Kelas XII Program Keahlian Administrasi Perkantoran di SMK Negeri 1 Surakarta Tahun ajaran 2016/2017 . Jurnal Informasi dan Komunikasi Administrasi Perkantoran , Volume 2, No 2 . Alwisol. (2008). Psikologi Kepribadian. Malang: UMM Press. Andreas, H., & Damian, L. (2007). Holland's Secondary Constructs of Vocational Interest and Career Choise Readiness of Secondary Students Measures for Related but Different Constructs. Journal of Individual Differences , 205-218. Anoraga, P. (2009). Psikologi Kerja. Jakarta: Rineka Cipta. Ardana, Komang,. et al. (2008). Perilaku Keorganisasian, Yogyakarta: GrahaIlmu. BPS.(2019). Keadaan Ketenagakerjaan Provinsi Kalimantan Barat Agustus 2019.Di akses dari: https://kalbar.bps.go.id/publication/2019/08/16/ 5bfa1ecd5b0cf472e92cc114/provinsi-kalimantan-barat-dalam-angka-2019. html Cahalpin J, P. (2006). Kamus lengkap psikologi (Terjemahan Kartini Kartono). Jakarta: PT Raja Grafindo Persada. Chuway, B. (2002). Human Resource Management. Jakarta: PT Elex Media Kumputindo Dalyono, M. (2005). Psikologi Pendidikan. Jakarta: Rineka Cipta. Damasanti, Revina, I. (2014). Kesiapan Kerja Ditinjau dari Motivasi Kerja, Sikap Kewirausahaan, dan Kompetensi Keahlian Busana Wanita pada Siswa SMKN. Jurnal Pendidikan Sains, Vol 2, No 2, 114-124 Diani, T. M., & Sumiati, A. (2018). The Influence of Internship and Career Guidance Toward the Work Readiness of the 12th Accounting Graders Of SMK Negeri 31 Jakarta For Academic Year 2017/2018. Econozains , 93-102. Djali. (2008). Proses Belajar Mengajar. Jakarta: Bumi Aksara. Fattah, N. (2009). Landasan Manajemen Pendidikan. Bandung: PT Remaja Rosdakarya. FEB.UNTAN.(2019). Profil Fakultas Ekonomi dan Bisnis Universitas Tanjungpura. Diakses dari https://feb.untan.ac.id Fiest, J., & Gregory, F. (2010). Theory of Personality, 7th ed, Penerjemah: Smita Prathita Sjahputri. Jakarta: Salemba Humanika. Fitriyanto, A. (2006). Ketidakpastian Memasuki Dunia Kerja Karena Pendidikan. Jakarta: Dineka Cipta. Ghozali. (2011). Aplikasi Analisis Multivariat dengan program SPSS. Semarang: Badan Penerbit Universitas Diponegoro. Hamalik, O. (2013). Proses Belajar Mengajar. Jakarta: Bumi Aksara. Hartoyo, T. B., Mardji, & Dardiri, A. (2018). Pengaruh model pembelajaran training within industry (TWI) dan pengalaman praktik kerja industri terhadap motivasi serta kesiapan kerja siswa SMK kompetensi keahlian teknik pemesinan se-kabupaten Gresik. Jurnal Pendidikan , Vol 1,No 8, 1633-1639. Ikdhan, A. M., & Adam, H. A. (2016). Dampak Jiwa Kewirausahaan dan Hasil Praktik Industri Terhadap Kesiapan Kerja Siswa SMK Paket Keahlian teknik Permesinan di Kota Makassae. Journal Media Komunikasi Pendidika Teknologi dan Kejuruan , 16-17. Kardimin, A. (2004). Strategi Melamar Kerja dan Bimbingan Karier. Yogyakarta: Pustaka Pelajar. Ketut, D. (1993). Bimbingan Karir di Sekolah-sekolah. Jakarta: Ghalia Indonesia Khairani, D., Wahyudin, A., & Pujiati, A. (2019). The Effect of Learning Achievement Accounting Through Industrial Work Practices, Work Competence and Self Efficacy as Intervening Variables on the Work Readiness of Class XII Program Students Accounting Skills in Semarang City. Journal of Economic Education , 133-140. Kurniawati, A., & Arief, S. (2016). Pengaruh Efikasi Diri, Minat Kerja, Dan Bimbingan Karir Terhadap Kesiapan Kerja Siswa SMK Program Keahlian Akuntansi. Economic Education Analysis Journal , 363-376. Kusasi, Muhammad. (2012). Pengaruh Budaya Organisasi,Efikasi Diri,Dan Kepuasan Kerja Terhadap Motivasi Kerja Pegawai Kanwil Kementrian Agama Provinsi Kaltim. Jurnal Psikostuditas Universitas Mulawarman , Vol 1, No 2, 102-117. Kusbiyantari, W., Sukarno, H., & Handayani, Y. I. (2019). Work Readiness Reviewed From Learning Achievement Of Computer Accounting Subject, Career Guisance, And Work Motivation of Class XII Students Accounting Skill Program of SMK Negeri 1 Suboh Situbondo. Higher Education of Economic Mandala , 56-63. Kusnaeni, Y., & Martono, S. (2016). Pengaruh Persepsi Tentang Praktik Kerja Lapangan,Informasi Dunia Kerja dan Motivasi Memasuki Dunia Kerja terhadap Kesiapan Kerja siswa SMK . Economic Education Analysis Journal , 16-29. Luthan, F. (2006). Perilaku Organisasi. Yogyakarta: Andi. Mardapi, Djemari. (2008) Teknik Penyusunan Instrumen Tes dan Non Tes,Yogyakarta: Mitra Cendikia Press Mustikawanto. (2019). Effect of Competency, Work Motivation, Industrial Work Experience and Facilities on the Readiness of Work for Senior High School Graduates in Electo Expertise Programs. Innovation of Vocational Technology Education . Narendra, Gilang. (2017). pengaruh Efikasi Diri Terhadap Kepuasan Kerja Dengan Motivasi Sebagai Variabel Intervening Pada PDAM Surya Sembada kota Surabaya. Jurnal Ilmu Manajemen , Vol 3, No 3,. Nurcahyono, E. (2015). Praktik Kerja Industri (PrAKERIN) dan Kontribusinya terhadap Kesiapan kerja Siswa Kelas XII SMK Negeri 1 Pati . Economic Education Analysis Journal . Purnama, N., Suryani, N., & Sapuroh. (2018). The Influences of Industry Internship, Career Guidance, and Working World Information to the Students Work Readiness of Grade XI SMK Palebon Semarang in Academic Year 2017/2018. in International Conference on Economics,Business and Economic Education,KnE sOCIAL sCIENCES , 273-288. Riyanto, Y. (2010). Metodologi Penelitian Pendidikan. Surabaya: SIC. Robbins, P. S. (2007). Perilaku Organisasi: Konsep, Kontroversi, Aplikasi. Jakarta: PT. Prenahalindo. Rosara, D. B., Harini, & Nugroho, J. A. (2018). Pengaruh Pengalaman Praktik Kerja Industri dan Motivasi memasuki Dunia Kerja terhadap Kesiapan Kerja Peserta Didik SMK Kristen 1 Surakarta Tahun Angkatan 2017/2018. Jurnal Pendidikan Bisnis dan Ekonomi , Volume 4 No 1. Rusydi, M. I., & Sukardi, T. (2019). The Effect of Maching Practical Achievment, Industrial Work Practice and Vocational Guidance on work Readiness of Mechanical Engineering Students Of Vocational High School in Karanganyar. International Journal of Education and Social Science Research , 176-184. Seo, B. M., & Bartunek, M. J. (2006). The role of affective experience in work motivation. Academy of Management , 29 (3):423-439. Sholihin, M., & Ratmono, D. (2013). Analisis SEM-PLS dengan WrpPLS3.0 untuk Hubungan Nonlinier. Penelitian Sosial dan Bisnis , Andi. Sirsa, I Made. (2014). Kontribusi Ekspektasi Karier,Motivasi Kerja, dan Pengalaman Praktik Kerja Industri terhadap Kesiapan Kerja Siswa Kelas XII SMK Negeri 2 Seririt. Jurnal Penelitian Pascasarjana . Slemato. (2010). Belajar dan Faktor-Faktor yang Mempengaruhinya. Jakarta: Rineka Cipta. Solimun., & Fernandes, A. (2017). Metode Statistika Multivariat Pemodelan Persamaan Struktural (SEM) Pendekatan WarpPLS. Malang: UB Press Stevani. (2015). Pengaruh Praktek Kerja Industri (Prakerin) dan Keterampilan Siswa terhadap Kesiapan Memasuki Dunia kerja Siswa Administrasi Perkantoran SMK N 3 Padang. Journal of Economic and Economic Education , 185-195. Sugiyono. (2014). Metode Penelitian Kuantitatif, kualitatif, dan R& D . Bandung: Alfabeta. Syahodih, Nana. (2009). Landasan Psikologi Proses Pendidikan. Bandung: PT Remaja Rosdikarya. Uno, H. (2014). Teori Motivasi dan Pengukurannya. Jakarta: Bumi Aksara. Utami, Y. G., & Hudaniah. (2012). Self efficacy dengan kesiapan kerja siswa Sekolah Menengah Kejuruan. Jurnal Ilmiah Psikologi Terapan , Vol 01, No 1, 40-52.  Wahyuda,S,V. (2018). Pengaruh Praktek Kerja Lapangan dan Motivasi Memasuki Dunia Kerja Terhadap Kesiapan Kerja Mahasiswa Pendidikan IPS Angkatan 2014 Universitas Islam Negeri Maulana Malik Ibrahim Malang. (skripsi yang dipublikasikan) Universitas Islam Negeri Maulana Malik Ibrahim, Malang Widoyoko, E. P. (2014). Teknik Penyusunan Instrumen Penelitian. Yogyakarta: Pustaka Pelajar. Winkel, & Hastuti. (2007). Bimbingan dan Konseling di Institusi Pendidikan. Yogyakarta: Media Abadi. Zulaehah, A., Rustiana, A., & Sakitri, W. (2018). pengaruh minat kejuruan,praktik kerja industri dan efikasi diri pada kesiapan kerja. Economic Education Analysis Journal , hal: 526-542.